2004
DOI: 10.1097/01.tp.0000133530.26680.dc
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis of Renal-Allograft Rejection: Correlation with Histopathologic Evaluation and Antirejection-Therapy Resistance

Abstract: Real-time RT-PCR quantification of the over-expression of the granzyme B gene in kidney-graft biopsies has proved to be as reliable in detecting acute rejection as histologic assessment. Furthermore, we demonstrate that the simultaneous measurement of the mRNA up-regulation of Fas ligand might represent an efficient new tool for the prediction of pejorative outcome of acute rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 25 publications
(27 reference statements)
2
35
0
Order By: Relevance
“…Upregulation of intragraft granzyme B and perforin also has been seen, again supporting the role of the cytotoxic T cell in allograft rejection (63). This observation also has been confirmed using real-time technology with high sensitivity (90%) and specificity (74%) for granzyme B as well as FasL (64). Moreover, the presence of enhanced expression of FasL more often was associated with therapeutic resistance to treatment.…”
Section: What More Can the Biopsy Tell Us?supporting
confidence: 56%
“…Upregulation of intragraft granzyme B and perforin also has been seen, again supporting the role of the cytotoxic T cell in allograft rejection (63). This observation also has been confirmed using real-time technology with high sensitivity (90%) and specificity (74%) for granzyme B as well as FasL (64). Moreover, the presence of enhanced expression of FasL more often was associated with therapeutic resistance to treatment.…”
Section: What More Can the Biopsy Tell Us?supporting
confidence: 56%
“…We previously demonstrated that the activity levels of the cytotoxic molecules Granzyme B (GB) and Fas ligand and the regulatory T cell (Treg) marker Foxp3, from the intragraft infiltrate of biopsies with BL changes, are intermediate, between those associated with TCMR and absence of rejection. 6,7 We also quantified the Foxp3/GB ratio to determine the relative proportions of alloaggressive and graft-protecting T cells. T cell infiltrate from biopsies with BL changes had a significantly higher ratio than in grade IA acute rejection biopsies, although the distribution of both markers was heterogeneous in all groups.…”
mentioning
confidence: 99%
“…This indicates that the presence of cytotoxic lymphocytes within an allograft is not necessarily harmful. Several studies have already shown comparable results employing biopsy material or urine [5,6,8,9,10,11,12], commonly demonstrating CTL-associated gene expression in kidneys without rejection. Nevertheless, levels of perforin and granzyme B increased with Banff rejection grades.…”
Section: Discussionmentioning
confidence: 70%
“…Recent studies emphasized the importance of T lymphocytes, but also of B cells in rejection and immunologic injury [1,2,3,4]. Detection of cytotoxic T cell transcripts, such as granzyme B, perforin or granulysin, in RNA extracts from transplanted kidneys, urine or peripheral blood allowed reliable diagnoses of acute rejection episodes [5,6,7,8,9,10,11], even at the subclinical level [12]. Furthermore, inflammatory proteins involved in fibrogenesis or cellular senescence were reported to be activated in chronically deteriorating transplants [13,14,15].…”
Section: Introductionmentioning
confidence: 99%